Optimization of ultrasound-assisted extraction for the maximum quantity and quality of phenolics from Stachys lavandulifolia. Issue 11 (24th July 2017) - Khoigani, Soroush Rahimi; Rajaei, Ahmad; Goli, Sayed Amir Hossein
ABSTRACT: The response surface methodology was used to evaluate the effects of extraction time, power of ultrasound, liquid to solid ratio, and solvent composition on the quantity and quality (from aspect of antioxidant activity) phenolics of Stachys lavandulifolia . The best extraction time, power of ultrasound, liquid to solid ratio, and solvent composition for both the quality and quantity of phenolics were 14 min, 300 W, 40 (v/w), and 57% methanol, respectively. Only the liquid to solid ratio was effective on the quality of phenolics. Also, the comparison between the ultrasound-assisted extraction and maceration methods showed the suitability of ultrasound-assisted extraction for extracting phenolics from this plant.